Scrotal migration of the abdominal end of the ventriculoperitoneal shunt - Fatih Karatas; Muhammed Erkam Yuksek; Busra Gul; Mehmet Kenan; Mehmet Fatih Erdi (Egyptian Journal of Neurosurgery)
Abstract Background The most common treatment of hydrocephalus is ventriculoperitoneal shunt (VPS) operation. Shunt dysfunction may develop in patients with ventriculoperitoneal shunt. The most common causes of shunt dysfunction, which are more common in pediatric patients, are infection, obstruction, visceral injury, pseudocyst formation, and excessive or inadequate drainage. Shunt migration is a rare complication of VPS operation, and the shunt catheter may migrate to the gastrointestinal tract, scrotum, bladder, and other organs. Revision surgery is a safe treatment option in most cases of shunt dysfunction or migration. Case presentation In this report, a 2-year and 10-day-old baby patient was observed to have bilateral hydrocele in the outpatient clinic follow-up after the VPS operation, and after radiological imaging, it was determined that the shunt peritoneal catheter was in the scrotum. The patient underwent shunt revision surgery. Conclusion Although malposition of the VPS peritoneal catheter is not always an emergency, reinsertion and surgical revision should be done promptly due to the risk of perforation due to malposition. Close follow-up of patients with VPS is important for early diagnosis and treatment of complications.